Antibodies to α5 chain of collagen IV are pathogenic in Goodpasture's disease. (June 2016) - Cui, Zhao; Zhao, Ming-hui; Jia, Xiao-yu; Wang, Miao; Hu, Shui-yi; Wang, Su-xia; Yu, Feng; Brown, Kyle L.; Hudson, Billy G.; Pedchenko, Vadim
Abstract: Autoantibody against glomerular basement membrane (GBM) plays a direct role in the initiation and development of Goodpasture's (GP) disease. The principal autoantigen is the non-collagenous domain 1 (NC1) of α3 chain of collagen IV, with two immunodominant epitopes, EA -α3 and EB -α3. We recently demonstrated that antibodies targeting α5NC1 are bound to kidneys in GP patients, suggesting their pathogenic relevance. In the present study, we sought to assess the pathogenicity of the α5 autoantibody with clinical and animal studies. Herein, we present a special case of GP disease with circulating autoantibody reactive exclusively to the α5NC1 domain. This autoantibody reacted with conformational epitopes within GBM collagen IV hexamer and produced a linear IgG staining on frozen sections of human kidney. The antibody binds to the two regions within α5NC1 domain, EA and EB, and inhibition ELISA indicates that they are targeted by distinct sub-populations of autoantibodies. Sequence analysis highlights five residues that determine specificity of antibody targeting EA and EB epitopes of α5NC1 over homologous regions in α3NC1. Furthermore, immunization with recombinant α5NC1 domain induced crescentic glomerulonephritis and alveolar hemorrhage in Wistar-Kyoto rats. Thus, patient data and animal studies together reveal the pathogenicity of α5 antibodies. Given previously documented cases of GP disease with antibodies selectively targeting α3NC1 domain, our data presents a conundrum of why α3-specific antibodies developing in majority of GP patients, with α5-specific antibodies emerged in isolated cases, the answer for which is critical for understanding of etiology and progression of the GP disease. Highlights: Antibody against α5 non-collagenous domain (NC1) of collagen IV induces Goodpasture's (GP) disease. Autoantibodies target two conformational epitopes, EA and EB, in α5NC1 domain. Structural analysis identified key epitope residues for antibody binding. Immunization with α5NC1 domain induces glomerulonephritis and lung hemorrhage in WKY rats. Occurrence of autoantibodies targeting α3NC1 and α5NC1 presents a conundrum for the etiology of GP disease.